The Analysis of Apoptosis in Ameloblastoma: Evaluation of Bcl-2, Bcl-X, Bax, Bak - Ferry Sandra; Norifumi Naksmura; Hiroshi Takeuchi; Takeshi Misuyasu; Yuji Shiratsuchi; Masamichi Ohishi (Faculty of Dentistry, Universitas Indonesia, 2015)
The apoptotic behavior of ameloblastomas was studied using antibodies against the apoptosis related proteins, Bcl-2, Bcl-X, Bax and Bak. Most of the outer layer cells were predominantly stained by the antimodulating proteins, Bax and Bak. Among the Bcl-2 family, Bcl-2 was the most ubiquitously expressed protein in ameloblastomas, while Bcl-X was expressed in the greatest concentrations. The acanthomatous areas overexpressed the apoptosis modulating proteins, especially Bak. The outer layer, whose cells had higher apoptotic inhibitor activity than inner layer cells, is suggested to be an active part.